Computed Tomography-guided Cryoablation for Adrenal Pheochromocytoma: Safety and Clinical Effectiveness. Issue 5 (October 2019) - Zhang, Wei; Shi, Yi-Bing; Zhuang, Zhi-Xiang; Wang, Jiu-Ping; Sun, Li-Jun; Fu, Yu-Fei
Abstract : Purpose: To evaluate the safety and clinical effectiveness of computed tomography (CT)-guided cryoablation for adrenal pheochromocytoma (AP). Materials and Methods: From July 2015 to October 2018, we observed 8 patients that underwent CT-guided cryoablation for AP. The blood pressure and pulse before treatment did not exceed 150/90 mm Hg and 90 times/min, respectively. Complete ablation rate, clinical success rate, and long-term outcomes were analyzed. Results: A total of 8 patients with 8 APs were treated by CT-guided cryoablation. The mean duration of the procedure was 67.5±4.6 minutes. No patient achieved complete ablation, yet the clinical success rate was 100%. The mean metanephrine decreased from 61.7±11.1 to 2.0±1.1 nmol/L ( P <0.001). Hypertensive crisis was found in 5 (67.5%) patients during the procedure. During a mean follow-up of 16.9±13.4 months, no patient experienced tumor progression. Conclusion: CT-guided cryoablation is an effective method for patients with AP.